The islamic revolutions: a photographic analysis - Rey, Pablo (Historia y Comunicación Social, 2014)
In the present paper it is analyzed the presence of violence in the graphic news contents anput the islamic revolutions of the Arab Spring, and how it could modify the perception of the facts related in that news. In addition, it is compared how high is the violence grade in the most important Spanish newspapers.
Keywords: Arab Spring; media; photography; revolution; conflicto